2018
DOI: 10.1007/s00404-018-4777-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of labor epidural analgesia on maternal–fetal outcomes: a retrospective cohort study

Abstract: Implementation of labor epidural analgesia increased the vaginal delivery rate and use of labor epidural analgesia is safe to parturients and fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 19 publications
6
37
2
1
Order By: Relevance
“…A similar result was seen in studies by Rouse et al, 19 Herrera-Gómez et al 8 and Wisborg et al 20 Conversely, a recent Cochrane meta-analysis by Anim-Somuah et al 14 concluded that EA is not associated with a higher rate of NICU admission. Previous studies by Wang et al 62 and Soncini et al 21 also did not find an association between EA and NICU admission. The difference in observation could be partially due to the difference in the NICU admission criteria of different institutions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A similar result was seen in studies by Rouse et al, 19 Herrera-Gómez et al 8 and Wisborg et al 20 Conversely, a recent Cochrane meta-analysis by Anim-Somuah et al 14 concluded that EA is not associated with a higher rate of NICU admission. Previous studies by Wang et al 62 and Soncini et al 21 also did not find an association between EA and NICU admission. The difference in observation could be partially due to the difference in the NICU admission criteria of different institutions.…”
Section: Discussionmentioning
confidence: 75%
“…6,7,17,54,61 None of them found any correlation between EA and 5 minute Apgar score. A recent study by Wang et al 62 also found no association between EA and Apgar score at one or 5 minutes. The correlation of low 1 minute Apgar with epidural analgesia observed by Hincz Petal 59 and Herrera-Gómez et al 8 might be attributable to the difference in the opioid used.…”
Section: Discussionmentioning
confidence: 86%
“…According to the data collected from Shijiazhuang Obstetrics and Gynecology Hospital where the project was rst introduced in 2008, the rate of overall CD decreased from 40.5% to 33.6% in the period when the rate of neuraxial labor analgesia increased from 0 to 33.5% [20]. At the second A liated Hospital, Wenzhou Medical University, Wang Q found that as the labor epidural analgesia rate increased from 0 to 57%, the vaginal delivery rate increased, and cesarean delivery rate decreased by 3.5%, at the same time the rate of episiotomy and severe perineal injury were decreased [21] . Our results are in accordance with those observational studies on the use of NA with the help of NPLD [7,[20][21] .…”
Section: Discussionmentioning
confidence: 98%
“…At the second A liated Hospital, Wenzhou Medical University, Wang Q found that as the labor epidural analgesia rate increased from 0 to 57%, the vaginal delivery rate increased, and cesarean delivery rate decreased by 3.5%, at the same time the rate of episiotomy and severe perineal injury were decreased [21] . Our results are in accordance with those observational studies on the use of NA with the help of NPLD [7,[20][21] . In our study, before the implement of NA, the rates of overall CD and MRCD were stable and high from January 1 st to May 30 th 2015, but with the increase of usage of NA, both of them were dropped.…”
Section: Discussionmentioning
confidence: 99%
“…There are lots of studies in which the effects of epidural in labor and long term fetal status are analyzed [31][32][33][34][35][36]. Most of them conclude that there are similar perinatal outcomes in patients undergoing epidural analgesia during labor and those without epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%